Joyce Cary's Technique Of Story-Telling: A Study On The Angle Of Vision And Character-Building - Khan, Imam Alam (Advances in Social Sciences Research Journal, 2019)
Joyce Cary (1888–1957) is an original novelist. He is a challenging writer of famous novels who is, no doubt, inimitable and amazingly unique. He is a moralist, a traditionalist, and a conservative who can never think of the irrational dominating the rational. Like other great artists, Cary also has a theme or an idea of life profoundly felt and founded in some personal and compelling experiences. A study of Cary's novels presents a vibrant and comprehensive idea of the world, which constitutes his visions and forms his original characterization. And, this is the basis of all sixteen novels he has written, and tried to build his strong characters through his angle of vision. Legouis and Cazamian write in ‘History of English Literature’, “He made use of everything; his Irish birth, African contacts and the intuitive vision of modern times.” (Legouis & Cazamian, P-1385) He regards freedom as the fundamental reality of life, much in the same way as Conrad believes that the world rests principally on the idea of fidelity; or as Henry James regards man's desire to live as the great truth about life. His footing is as Hardy holds the injustices of life the cruelty of blind fate, destroying innocent and guilty alike to be the fundamental truth about life, or as Somerset Maugham thinks that man is in constant search for freedom from bondage of all kinds. Joyce Cary is an adept craftsman who takes great pains in choosing the angle of vision from which he is to narrate his story. His novels reveal how he has experimented with various narrative techniques in order to make his meaning unmistakably flawless to the reader. Cary's first three novels, ‘Aissa Saved’, ‘An American Visitor’, and ‘The African Witch’, exhibit his skill in employing the most common technique of story-telling, the omniscient author's view-point, which is also known as direct narrative, or epic manner of storytelling. “His stories absorb our interests, and take us to a new world, away from our routine work where we feel, experience and enjoy”. (Khan, Imam Alam: P-60) So, this research paper is going to investigate whether Joyce Cary, the author of sixteen novels, has the author’s assumed omniscience method or not, and which particularly suits Cary or not? Does it enable him to express his vision of life easily and effectively? Are his other techniques of story-telling are unique, quite more impressive as well as more effective as the direct narrative methods? This paper is going to discuss the questions in detail to substantiate the unique techniques used by Cary.